Instrument Appropriateness On The Assessment Of Fourth Grade Science Learning Outcomes In Elementary Schools - Widyaningsih, Ida Ayu Tri; Dibia, I Ketut (International Journal of Elementary Education, 2020)
The existence of problems in the assessment quality is caused by the learning process that is not accompanied by suitable instruments, affecting student learning outcomes. This study aimed to analyze the quality of the instruments used in assessing science learning outcomes. This research is development research using the ADDIE model. The subject of this study was the validity and reliability of the science’s learning outcome assessment instrument. The data collection method used in this study was to provide validation sheets to two experts in science. The instruments used in this study were the instrument validation sheet and the multiple-choice objective test developed to analyze reliability. The data analysis technique used in this research is quantitative statistical analysis techniques. Based on the analysis results, the results obtained were that the instrument's average validity was 1.00, and the reliability coefficient was 0.66. This research concludes that the instrument of science learning outcomes obtains a high level of validity and reliability. This research implies that the instrument of student learning outcomes developed has been tested for its validity and reliability. It is suitable to be used to measure the learning outcomes of Fourth- Grade elementary school students.